Pengendalian Hayati Penyakit Layu Bakteri Tembakau: 1. Isolasi Bakteri Antagonis - Triwidodo Arwiyanto (Jurnal Perlindungan Tanaman Indonesia, 1997)
Three hundred strains of fluorescent pseudomonad and 120 strains of Bacillus spp. were isolated from the rhizosphere of Mimosa invisa L. Fluorescent pseudomonad was isolated on King s B while Bacillus spp. were isolated on Tryptic Soy Agar medium. Each media were supplemented with 100 ppm cycloheximide to suppress fungal growth. All isolated strains were tested for their capability to suppress the growth of Pseudomonas solanacearum on appropiate media. Most of fluorescent pseudomonad inhibited the growth of the pathogen with an inhibition zone from 1 mm to 16 mm. The mechanism of growth-inhibition was bacteriostatic and some of them were bactericidal. Sixty six out of 120 strains of Bacillus spp. produced defined inhibition zones on the media. The zone of growth-inhibition varied from 2 to 14 mm and the mechanism of inhibition was bactericidal. Several strains of those two bacterial marga exhibited non-antagonistic activity toward each other.